Pengaruh Pemberian Amelioran Dregs pada Tanah Gambut Terhadap Pertumbuhan dan Akumulasi Logam Berat (Pb, Cr, Se, Ni) dalam Beras - Melda Octvaiana; Nelvia ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research aims to determine to the effect of ameliorant dregs the growth of rice plants and the accumulation of heavy metals Pb, Ni, Cr and Se. This study was conducted at Agriculture Faculty greenhouses, University of Riau and also Soil Laboratory, and Campus Bina Widya km 12.5 Kelurahan Simpang Baru, Pekanbaru lasted from August to December 2012. This study was carried out experimentally  used Completely Raandomized Design (CRD), consists of 4 treatment (0, 20, 40, 60 ton/ha). The result shows that the application dregs 20 tons/ha increased plant height, maximum number of tillers, grain weight and pithy rice. Ameliorant dregs dosing with doses of 20, 40 and 60 ton/ha reveal small influence on the accumulation of heavy metals (Se and Cr) even may not be detected at all the presence of heavy metals (Pb and Ni)  the grain so there is poison in rice plants. Keywords : Ameliorant Dregs, peat, rice.Heavy Metals